Zakat Distribution and Programme for Sustaining Muallaf Belief and Thought (Sains Humanika, 2013)
Zakat is one of the pillars of Islam that emphasises the socio-economic development. Any discussion onzakat in the context of worship cannot be disconnected from the socio-economic factor, especially inaiding the underprivileged. The primary purpose of zakat is to redistribute wealth of the society amongthe poor. Zakat is not purely welfare-oriented that relies on the contribution of the giver but an obligationthat must be carried out to qualified recipients. Therefore, it is pertinent that the management of zakat ismade efficient to ensure that the rights of the recipients and the society, in general, will not be put injeopardy. The question is then raised regarding the type of zakat distribution or programmes pertaining tothe asnaf Muallaf. The objective of this article is to explore zakat distribution programmes for sustainingmuallaf belief (Tauhid) and thoughts (Iman). The methodology of this article is based on qualitativeresearch through document analysis and interview with zakat officer. This article has revealed that a hugeamount had been allocated for the development of asnaf Muallaf. It is conclude that, State IslamicReligious Council needs to continuously improve a comprehensive programmes that focus on sustainingthe Muallaf belief (Tauhid) and thoughts (Iman).
Keywords: Muallaf; zakat distribution; muallaf programmes; Selangor State Islamic Religious Council